2017
DOI: 10.1371/journal.pone.0173616
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and genetic influences on hemostasis in a Yup’ik Alaska Native population

Abstract: Fish and marine animals are important components of the subsistence diet of Alaska Native people, resulting in a high ω3 PUFA intake. The historical record for circumpolar populations highlights a tendency for facile bleeding, possibly related to ω3 PUFA effects on platelet activation and/or vitamin K-dependent clotting factors. To evaluate these two scenarios in Yup’ik people of southwestern Alaska, we examined the association between dietary ω3 PUFA intake and activities of clotting factor II, V, fibrinogen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…As reported previously, inheritance of the CYP4F2*3 allele was associated with long‐term (PIVKA‐II) vitamin K status in our study population . CYP4F2 has been shown to act as an ω‐hydroxylase to VK1 and MK4, and the V433M coding variant defining the *3 allele is associated with a higher warfarin dose requirement of ≈1 mg d –1[ ] and a reduced risk of a major bleeding event in patients receiving warfarin therapy chronically .…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…As reported previously, inheritance of the CYP4F2*3 allele was associated with long‐term (PIVKA‐II) vitamin K status in our study population . CYP4F2 has been shown to act as an ω‐hydroxylase to VK1 and MK4, and the V433M coding variant defining the *3 allele is associated with a higher warfarin dose requirement of ≈1 mg d –1[ ] and a reduced risk of a major bleeding event in patients receiving warfarin therapy chronically .…”
Section: Discussionsupporting
confidence: 74%
“…a) Data for this group of 659 study participants is a subset of the larger cohort previously reported …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations